2019
DOI: 10.1016/j.bjorl.2018.05.012
|View full text |Cite
|
Sign up to set email alerts
|

Serum- and glucocorticoid-inducible kinase 3 is a potential oncogene in nasopharyngeal carcinoma

Abstract: Serum- and glucocorticoid-inducible kinase 3 expression was more frequently observed as the nasopharyngeal epithelium progresses from normal tissue to carcinoma. This suggests that serum- and glucocorticoid-inducible kinase 3 contributes to the multistep process of NPC carcinogenesis. Serum- and glucocorticoid-inducible kinase 3 represents a target for nasopharyngeal carcinoma therapy, and a basis exists for the further investigation of this adjuvant treatment modality for nasopharyngeal carcinoma.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 38 publications
0
4
0
Order By: Relevance
“…The pathophysiology behind the association between stressful events and cancer is attributed to the release of glucocorticoids through the hypothalamic-pituitary axis molecular pathways and in beta-adrenergic signaling through the sympathetic nervous system [28,32]. The release of catecholamines can stimulate the transcription of various proteins involved in the regulation of cellular growth, differentiation and the transcription of various genes, which can result in the onset and progression of various malignancies [33][34][35]. The role of cortisol in tumor cell proliferation has also been described in various malignancies.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The pathophysiology behind the association between stressful events and cancer is attributed to the release of glucocorticoids through the hypothalamic-pituitary axis molecular pathways and in beta-adrenergic signaling through the sympathetic nervous system [28,32]. The release of catecholamines can stimulate the transcription of various proteins involved in the regulation of cellular growth, differentiation and the transcription of various genes, which can result in the onset and progression of various malignancies [33][34][35]. The role of cortisol in tumor cell proliferation has also been described in various malignancies.…”
Section: Discussionmentioning
confidence: 99%
“…The role of glucocorticoid-activated receptors in cell growth and survival has been described in various studies [17,33]. For example, glucocorticoid-inducible kinase 3 has been described as a potential oncogene in nasopharyngeal carcinoma [34]. A few studies have shown the impact of circulating catecholamines and glucocorticoid levels in oral cancer: that chronic stress is associated with increased IL-6 expression in humans with oral cancer and increased VEGF expression with tumor size in oral carcinoma mouse models via increased circulating catecholamines and glucocorticoids [18,35].…”
Section: Discussionmentioning
confidence: 99%
“…SGK3 silencing could suppress proliferation, survival and migration of NPC cells (Chen et al, 2019).…”
Section: Sgk3mentioning
confidence: 98%
“…Laser-based therapies, particularly photothermal therapy (PTT), have emerged as promising strategies for this purpose. [1][2][3][4] These therapies utilize agents with near-infrared (NIR) activity to absorb laser energy and convert it into heat, thereby inducing localized thermal damage, specifically to cancer cells. 5,6 By harnessing the power of PTT, it is possible to mitigate the toxic side effects associated with traditional chemotherapy.…”
Section: Introductionmentioning
confidence: 99%